ANALISIS RISIKO PENGOPERASIAN OVERHEAD CRANE DOUBLE GIRDER DI DIVISI KAPAl NIAGA PT PAL SURABAYA - Ryan Rizky Bikatofani (Universitas Airlangga, 2015)
ABSTRACTPT. PAL Surabaya operates Overhead Crane Double Girder tool every day. Those have some risks, for example squeezed, material crushed, fracture and passed away. The objective of the research was to value the level of risks on kapal niagadivision PT. PAL Surabaya. The type of this research was descriptive observational research with cross sectional approach. The research focuses on overhead crane double girder operation at kapal niaga division PT PAL Surabaya, consists ofoperation phase itself. Primary data collection by doing interview and observation, it was presented in a table, analyzed, and explained in descriptive way. The result showed there were 8 potential hazards on operation phase. Controlling type that most implementated was providing personal protective equipment (PPE) as 75%. That is quite significant and effective although there were still residual risks on 7 low potential hazards on preparation phase and 1 medium potential hazards on operation phase. PT PAL Surabaya has not done measurement the level of risks and suggested to do identification in details by noticing any hazards and risks in every job phase. Besides, the operator from the whole overhead crane doublegirder operation should have K3 (SIO) license and specific experience in operating overhead crane double girder, this suitable with Permenaker No 09/MEN/VII/2010.Keywords: risk assessment, overhead crane double girder, level of risks